Batman : Vol. 1, their dark designs - Tynion, James, IV; Ayala, Vita; Johnson, Phillip Kennedy, 1970-; Tamaki, Mariko; Watters, Dan (DC Comics, 2020)
"It's a new day in Gotham City, but not the same old Batman. With Bane vanquished and one of his longtime allies gone, Batman has to start picking up the pieces and stepping up his game. Batman has a new plan for Gotham City, but he's not the only one. Deathstroke has returned as well, under a mysterious new contract that could change everything"--